Enhancement of thermal neutron shielding of cement mortar by using borosilicate glass powder. (May 2017) - Jang, Bo-Kil; Lee, Jun-Cheol; Kim, Ji-Hyun; Chung, Chul-Woo
Abstract: Concrete has been used as a traditional biological shielding material. High hydrogen content in concrete also effectively attenuates high-energy fast neutrons. However, concrete does not have strong protection against thermal neutrons because of the lack of boron compound. In this research, boron was added in the form of borosilicate glass powder to increase the neutron shielding property of cement mortar. Borosilicate glass powder was chosen in order to have beneficial pozzolanic activity and to avoid deleterious expansion caused by an alkali–silica reaction. According to the experimental results, borosilicate glass powder with an average particle size of 13 µm showed pozzolanic activity. The replacement of borosilicate glass powder with cement caused a slight increase in the 28-day compressive strength. However, the incorporation of borosilicate glass powder resulted in higher thermal neutron shielding capability. Thus, borosilicate glass powder can be used as a good mineral additive for various radiation shielding purposes. Highlights: Borosilicate glass powder with an average particle size of 13 µm showed pozzolanic activity. Replacement of cement with borosilicate glass powder significantly reduced thermal neutron shielding capability. Borosilicate glass powder can be a good mineral additive for radiation shielding purpose.